Three-Dimensional Modeling of the Casing Effect in Onshore Controlled-Source Electromagnetic Surveys - Puzyrev, Vladimir; Vilamajo, E.; Queralt, P.; Ledo, J.; Marcuello, A. (Springer, 2016)
The presence of steel-cased wells and other infrastructure causes a significant change in the electromagnetic fields that has to be taken into consideration in modeling and interpretation of field data. A realistic and accurate simulation requires the borehole casing to be incorporated into the modeling scheme, which is numerically challenging. Due to the huge conductivity contrast between the casing and surrounding media, a spatial discretization that provides accurate results at different spatial scales ranging from millimeters to hundreds of meters is required. In this paper, we present a full 3D frequency-domain electromagnetic modeling based on a parallel finite-difference algorithm considering the casing effect and investigate its applicability on the borehole-to-surface configuration of the Hontomín CO2 storage site. To guarantee a robust solution of linear systems with highly ill-conditioned matrices caused by huge conductivity contrasts and multiple spatial scales in the model, we employ direct sparse solvers. Different scenarios are simulated in order to study the influence of the source position, conductivity model, and the effect of the steel casing on the measured data. Several approximations of the real hollow casing that allow for a large reduction in the number of elements in the resulting meshes are studied. A good agreement between the modeled responses and the real field data demonstrates the feasibility of simulating casing effects in complex geological areas. The steel casing of the well greatly increases the amplitude of the surface electromagnetic fields and thus improves the signal-to-noise ratio and the sensitivity to deep targets.